The scale of repeat prescribing – time for an update - Petty, Duncan R; Zermansky, Arnold G; Alldred, David P (BMC health services research, 2014)
Background The NHS spends billions of pounds annually on repeat prescriptions in primary care, but data on their extent and use is out of date. Understanding the scale of repeat prescribing and for whom it is prescribed is important for the NHS to plan services and develop policies to improve patient care. Method Anonymous data on prescription numbers and practice population demographics was obtained from GP computer systems in a large urban area. Searches were conducted in November 2011 to identify the numbers of repeat items listed on individuals’ repeat lists by sex and age. The proportion of all prescription items issued as repeats was identified by conducting searches on items issued as repeat and acute prescriptions. Results In the year of study 4,453,225 items were issued of which 3,444,769 (77%) were repeats (mean 13 items per patient/annum) and 1,008,456 (23%) acute prescriptions (mean 3.9 items per patient per annum). The mean number of repeat Items per patient was 1.87 (range 0.45 ages 0-9 years; 7.1 ages 80-89 years). At least one repeat medicine was prescribed to 43% of the population (range 20% for ages 0-9; over 75% for ages 60+). Conclusion A significant proportion of the population receive repeat prescriptions and the proportion increases with age. Whilst the proportion of repeat items to acute items has remained unchanged over the last two decades the number of repeat prescriptions items issued has doubled (from 5.8 to 13.3 items/patient/annum). This has implications for general practice workload, patient convenience, NHS costs and risk.